2008
DOI: 10.1590/s0103-50532008000500006
|View full text |Cite
|
Sign up to set email alerts
|

Infraspecific variability in the essential oil composition of Lychnophora ericoides

Abstract: A variação na composição química do óleo essencial das folhas em três populações silvestres de Lychnophora ericoides, com ou sem odor, indicou a presença de dois grupos de óleos em relação ao odor das amostras. O primeiro incluiu amostras de odor aromático contendo altas percentagens de -bisabolol (34 23%) e o-cimeno (8,4 6,9%). No grupo II, as amostras não apresentaram qualquer odor e os constituintes majoritários foram o óxido de cariofileno (11 9%) e o -elemeno (5,7 6,9%). Em todas as populações estudadas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Besides, the flavonoid patuletin is responsible for the anti-bacterial and anti-fungal effects of marigold flower [86]. Hexanal, 1-hexanol, 2-hexanol, nonanal, benzaldehyde, benzylealcohol, caryophyllene are responsible for the smell of carnation flowers though the terpene caryophyllene is the key anti-inflammatory component [87]. Lilac flowers also show some antiinflammatory effects due to the presence of various isoprenoids e.g.…”
Section: Aromatic Compounds Of Edible Flowers and Their Health Effect...mentioning
confidence: 99%
“…Besides, the flavonoid patuletin is responsible for the anti-bacterial and anti-fungal effects of marigold flower [86]. Hexanal, 1-hexanol, 2-hexanol, nonanal, benzaldehyde, benzylealcohol, caryophyllene are responsible for the smell of carnation flowers though the terpene caryophyllene is the key anti-inflammatory component [87]. Lilac flowers also show some antiinflammatory effects due to the presence of various isoprenoids e.g.…”
Section: Aromatic Compounds Of Edible Flowers and Their Health Effect...mentioning
confidence: 99%
“…It was found specimens with scent and without scent form two well-separated clusters. Scented species contained mainly a-bisabolol and o-cymene while species without scent contained higher quantities of caryophyllene oxide and d-elemene (Lyra et al, 2008). GC/MS was also used for the separation and quantitative determination of volatile aroma compounds of Japanese sour citrus fruit (Citrus nagato-yuzukichi).…”
Section: Foods and Food Productsmentioning
confidence: 99%
“…The calculations demonstrated that healthy dogs and dogs infected by Leishmania infantum can be discriminated by the method. It was established that 2-hexanone, benzaldehyde and 2,4-nonadienal play a decisive role in the discrimination process (de Oliveira et al, 2008). SPME coupled with GC/MS has also been employed for the determination of volatile compounds emitted from 17 bacterial species.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…clavel tienen actividades antiinflamatorias debido a la presencia del terpeno cariofileno (Lyra et al, 2008). Del mismo modo, las actividades antiinflamatorias, antituberculosas y anticancerígenas de las flores de crisantemo se deben a la presencia de 3onohidroxiterpenos, triterpensarnidiol, faradiol y heliantriol (Inoue et al, 1998;Akihisa et al, 1996;2005).…”
Section: El Aroma Y Sabor En Las Flores Comestiblesunclassified